Le «paradoxe de l’imperfectivité» dans la perspective de la théorie de S. Karolak - Nowakowska, Małgorzata (Neophilologica, 2010)
This article deals with the so called “Imperfective paradox” and the way in which this paradox is explained by S. Karolak’s theory of aspect. The “Imperfective paradox” concerns the accomplishment verbs (Vendler) in the progressive form, which is generally considered in English as the imperfective aspect. One of the consequences of this paradox is that for instance the sentence John was drawing a circle doesn’t imply John drew a circle. In the theory of S. Karolak this paradox disappears. Theses verbs are analyzed as telic configuration of aspects or limitative-telic configuration of aspects.